Combined Factor VIII and IX Inhibitors in a Girl - Reussi, C; Altman, R; Rouvier, J; Maino, R (Thrombosis and Haemostasis, 1966)
A case is described of a 5 year old child, who for several years presented a moderate haemorrhagic symptomatology. Tests have shown a deficiency due to clotting inhibitors; in the present case the inhibitors act against factors VIII and IX.